Szadek na tle sytuacji gospodarczej departamentu kaliskiego przełomu stuleci XVIII i XIX - Kowalczyk, Rafał Wiktor (Biuletyn Szadkowski, 2008)
After 1793 Szadek was included in Kalisz department in South Prussia province. The department was divided into 18 districts, of which Szadek was one. Prussian government attached great importance to the development of cities. They were intended to act as economic centres. Szadek was situated away from main transport routes and was not supplied with sufficient warehousing infrastructure to stimulate radical capitalist transformation. The towns along arterial roads experienced fast development. Prussian government, though deriving increasingly high revenues from the annexed provinces, supported the development of crafts, industry and trade. During the period 1793/94–1808 Szadek’s population grew to 972 inhabitants (30.9% growth). The period of Warsaw Duchy was very demanding financially because of high costs connected with the military requirements. A garrisonon of Duchy soldiers was stationed in Szadek, which was a great strain on the town’s budget. It hampered municipal development projects, which could not be implemented until the period of the Congress Kingdom. Despite difficult conditions Szadek showed a growth tendency, although it was weaker than in the period of Prussian rule. In 1810 the population grew to 1149. The situation worsened drastically in 1812, with the passage of the troops of Great Army, and subsequent passage of Russian troops in 1813–1815, which affected all towns in the Kalisz department.